Family Socioeconomic Status and Learning Engagement in Chinese Adolescents: The Multiple Mediating Roles of Resilience and Future Orientation - Chen, Jing-Jing; Jiang, Ting-Na; Liu, Ming-Fei (Frontiers in Psychology, 2021)
This research explores the mediating effects of resilience and future orientation on the relationship between family socioeconomic status (SES) and learning engagement within the context of Chinese culture based on the cognitive theory of social class. A total of 1245 junior high school students were recruited to complete an anonymous questionnaires regarding their family's objective and subjective SES, resilience, future orientation and learning engagement. The mediating effects were tested by stepped multiple linear regression. Results indicated that, (1) The relationships between objective and subjective SES, resilience, future orientation and learning engagement were significantly positive. (2) Resilience only mediated the relationship between subjective SES and learning engagement whereas future orientation mediated the relationships between objective/subjective SES and learning engagement. (3) Resilience and future orientation sequentially mediated the relationship between subjective SES and learning engagement. Current research has contributed to a better understanding regarding how family SES influences adolescent academic performance from the perspective of adolescent cognitive abilities. Additionally, it has provided implications for the prevention and intervention of poor adolescent academic performance due to low SES.